Comparison of International Contract Law UNIDROIT and Contract Law in Indonesia - Alifiyah Fitrah Rahmadhani (Jurnal Justiciabelen, 2025)
Increasing needs are the reason for seeking settlements so that their needs can be met. However, it should be noted that not only humans need to meet their needs, even countries need to meet needs that cannot be found in their own country. Just as humans need each other, countries also need help from other countries to fulfill what they don't have, so international trade contracts arise. Therefore, regulations were formed to become a legal umbrella for parties in international transactions. The purpose of writing is used to analyze the similarities and differences in the principles of UNIDROIT and contract law in Indonesia. The research method used is normative juridical research, namely legal research conducted by examining secondary data with an emphasis on library research. So that the results of the research and discussion of the differences and principles of UNIDROIT and contract law principles in Indonesia, even though there are slight differences between the two, UNIDROIT principles still follow national rules and principles.